Quel role jouent les plateformes dans le capital social des nomades numeriques ? - Clément marinos (Netcom)
In this article, we aim to highlight the importance of digital platforms, particularly the social network Facebook, in online relationships among digital nomads. To achieve this, we employ social capital theory, conducting both quantitative and qualitative analyses of user groups and posts. The results reveal a strong geographical dimension in the search for social capital, as well as a relative balance between bridging and bonding capital. We also underscore a limited presence of local actors on the social network, despite the richness of interactions among nomads, preferring virtual relationships among peers.